2022
DOI: 10.1111/trf.16972
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory reserve and pulse character: Enhanced potential to predict urgency for transfusion and other life‐saving interventions after traumatic injury

Abstract: Background Field triage of trauma patients requires timely assessment of physiologic status to determine resuscitative needs. Vital signs and rudimentary assessments such as pulse character (PC) are used by first responders to guide decision making. The compensatory reserve measurement (CRM) has demonstrated utility as an easily interpretable method for assessing patient status. We hypothesized that the ability to identify injured patients requiring transfusion and other life‐saving interventions (LSI) using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
(108 reference statements)
1
3
0
Order By: Relevance
“…This odds ratio comparison demonstrates the increased discriminatory ability of CRM to provide early prediction of the need for intervention and shows an improved ability to guide intraoperative resuscitation relative to standard vital sign measurements. Our findings also confirm results published from prior studies shown an increased discriminatory ability of CRM to predict need for transfusion in traumatic hemorrhage (9). The earlier detection of changing volume status using CRM during surgery and resuscitation observed in the present investigation provides the clinician with an adjunctive tool to supplement vital sign measures for enhanced patient care given the relationship between early intervention and improved clinical outcomes (1,4,6,10).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This odds ratio comparison demonstrates the increased discriminatory ability of CRM to provide early prediction of the need for intervention and shows an improved ability to guide intraoperative resuscitation relative to standard vital sign measurements. Our findings also confirm results published from prior studies shown an increased discriminatory ability of CRM to predict need for transfusion in traumatic hemorrhage (9). The earlier detection of changing volume status using CRM during surgery and resuscitation observed in the present investigation provides the clinician with an adjunctive tool to supplement vital sign measures for enhanced patient care given the relationship between early intervention and improved clinical outcomes (1,4,6,10).…”
Section: Discussionsupporting
confidence: 92%
“…However, we are unaware of any clinical investigations other than the current study reported here that have presented experimental results that support the ability of CRM for use in the intraoperative setting. Compensatory reserve measurement has been shown to display superior sensitivity and specificity for predicting reductions in central blood volume in human experimental protocols compared with other noninvasive measures of volume status (1–5) and increased ability to predict transfusion in trauma patients (9,10,13,18). Given that CRM is an algorithmic measurement of the summation of all physiologic compensatory mechanisms with an ability to detect hemorrhagic blood losses and track restoration of circulating volume during resuscitation, we hypothesized that the algorithm would provide novel assessment of patients undergoing a liver transplant surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations